BiometrÍa del molusco Anadara tuberculosa (Pelecypoda: Arcidae) en Punta Morales, Puntarenas, Costa Rica - Cruz, Rafael A.; Palacios, José A. (Revista de Biología Tropical, 1983)
Several biometric characteristics, sexual dimorphism and meat percentage were studied in a popula· tion of Anadara tuberculosa at Punta Morales, Costa Rica, from May, 1980 to April, 1981. Samples were ar· bitrarily divided into three size categories (1: 4247.5 mm; 2: 48-5 3.5 mm and 3: 54·59.5 mm). No sexual dimorphism was found in the length-weight ratio. Growth appears to be allometric. The best model to ex· press wet meat weight is the quadratic, with length being the most consistent parameter. It was also found that meat percentage was greater in those individuals of the first size category (20.34%), and smaller in individuals of size 3 (16.31 %. Mean meat percentage was estimated at 18.26%